PENGUJIAN TAHANAN ISOLASI DAN RASIO PADA TRAFO PS T15 PT INDONESIA POWER UP MRICA - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
Auxiliary transformers are the main equipment that is vital as voltage supplier to various equipment – equipment mounted on a plant. Without good maintenance it will affect the performance of transformer, based on research of Joko Susilo, Abdul Syahkur (2012) that maintenance of power transformer is done to maintain the effectiveness and endurance of electric power system so that the channelling is maintained well. This study aims to provide information on transformer condition early for PT Indonesia Power UP Mrica. Dwirahayu Widhiyanti (2016) argued to prevent damage caused some maintenance, among others, the examination of visual conditions, isolation testing and comparison of transformer. To perform isolation and ratio resistance testing, this test was conducted usng literature study method, which used the standard of IEC 60076-3:2000-03, ANSI C57.12.90 and PT PLN (Persero) P3B engineering sequence. In this test, the isolation resistance obtained and the ratio of the Auxiliary transformer in which the isolation resistance of PS T15 transformer is in good condition and bad condition because LV-G and HV-LV are between 1 - 1.1 HV-G and HV LV-G its value > 1.25, while the ratio test results on PS T15 transformer does not conform to the existing standard (ANSI Standard C57.12 .90) with results above the standard 0.5%, U phase6.39, phase V 6.91, phase W 6.91.